Dekanski narečni govor nekoč in danes - Todorović, Suzana (Slavia Centralis, 2025)
This article examines phonetic changes in the Dekani local speech on the basis of a manuscript report written by Tine Logar following a dialectological field research carried out in Dekani in 1955. The manuscript, which is kept at the Department of Dialectology of the Fran Ramovš Institute of the Slovenian Language at ZRC SAZU (Slovenian Academy of Arts and Sciences), as is normally the case, provides a comprehensive summary of the main phonological and morphological developments, and specific features in the dialect under scrutiny. Phonological findings made by Tine Logar are in this paper diachronically compared with records and available dialectal data and materials collected and published for the Dekani region in the period between 1955 and 2025. The main focus of the investigation is establishing which phonological features recorded by Logar are still present in the speech of older speakers, and assessing the extent (if any) to which they occur in the speech patterns of younger generations.
Keywords: diachronic study; diahrona raziskava; dialect change; dialectology; dialektologija; glasoslovje; phonetics and phonology; Rižana subdialect; rižansko podnarečje; Slovenian Istrian dialect; slovensko istrsko narečje; spreminjanje narečja